Penggunaan Media Ajar Berbasis Aplikasi Flipbook terhadap Hasil Belajar Materi IPAS Kelas V SDN Rejosari 01 - Juliati Anggraeni Fatma Asih; Ervina Eka Subekti; Lidya Septia Devega (Journal on Education, 2024)
The purpose of this research is to determine and analyze the learning outcomes of class V students at SDN Rejosari 01 before and after using flipbook application-based teaching media in the social and sciences subject material on natural appearances on land. Based on the results of interviews with class teachers and observations of the class V A environment it can be concluded that the facilities in the class are sufficient to support the use of technology-based learning media, so the researchers applied learning media based on the flipbook application in the social and sciences subject of natural appearance. The method used is quantitative research with a pretest- posttest design, with a sample size of 27 students. The instrument used in this research used multiple choice question sheets. The results of this research show that 11 students scored above the minimum completeness criteria (KKM) before using the flipbook application-based teaching media, with an average completion rate of 41%. Then, in terms of learning outcomes after using the flipbook application-based teaching media, 19 students scored above the KKM, with an average of 70% completion. It can be concluded that the learning outcomes for class V in the social and sciences subject material on natural appearances on land have increased in the completeness of learning outcomes students obtained by 29%.